Examination of the reliability and feasibility of two smartphone applications to assess executive functioning in racially diverse older adults. Issue 6 (2nd November 2022) - John, Samantha E.; Evans, Sarah A.; Kim, Bona; Ozgul, Petek; Loring, David W.; Parker, Monica; Lah, James J.; Levey, Allan I.; Goldstein, Felicia C.
ABSTRACT: Inclusion of Black participants in clinical research is a national priority. Mobile applications and remote data collection may increase study access for diverse populations. This study examined the reliability and feasibility of two mobile smartphone application-based cognitive measures in a diverse middle aged and older adult sample. Black (n = 44; M age = 59.93) and non-Hispanic white (NHW; n = 50; M age = 61.06) participants completed traditional paper-based neuropsychological testing and two app-based measures, Arrows and Number Match. Intraclass correlations demonstrated poor to moderate reliability (range: .417–.569) between performance on the app-based versions and performance on the traditional versions. Performance score differences by racial group were not statistically significant. Both Black and NHW participants rated the app-based measures as feasible and acceptable, though Black participants endorsed a stronger likelihood of future use. These findings add to the growing literature on remote cognitive testing .